MathOverflow will be down for maintenance for approximately 3 hours, starting Monday evening (06/24/2013) at approximately 9:00 PM Eastern time (UTC-4).

Post Undeleted by Sunni
Post Deleted by Sunni
2 latex fixed

Simple calculation shows $d_3=1, d_4=\frac{18p^3+11p^2-6p+1}{24p^3}, 30p^3d_5=6p^2(4+p)d_4+(p-1)[3p(3+2p)+(2p-1)(2+3p)]d_3$, and so $d_3>d_4>d_5$.

Assume $d_i>d_{i+1}>d_{i+2}$ and $6p^3(i+2)d_{i+2}\ge 6p^2(i+1+p)d_{i+1}+(p-1)[3p(i+2p)+(2p-1)(i-1+3p)]d_i$ for all $i\ge3$ .

Then $6p^3(i+3)d_{i+3}=6p^2(i+2+p)d_{i+2}+\frac{p-1}{p}[3p^2(i+1+2p)d_{i+1}+(2p-1)(i+3p)pd_i]6p^3(i+3)d_{i+3}=6p^2(i+2+p)d_{i+2}+\frac{p-1}{p}[3p^2(i+1+2p)d_{i+1}+(2p-1)(i+3p)pd_i]$< 6p^2(i+2+p)d_{i+2}+\frac{p-1}{p} $6p^2(i+2+p)d_{i+2}+\frac{p-1}{p} {6p^2(i+1+p)d_{i+1}+(p-1)[3p(i+2p)+(2p-1)(i-1+3p)]d_i }\le \le$ $6p^2(i+2+p)d_{i+2}+ \frac{p-1}{p} 6p^3(i+2)d_{i+2}=6p^3(i+3)d_{i+2}$, this shows $d_{i+3}< d_{i+2}$.

Moreover, $6p^3(i+3)d_{i+3}=6p^2(i+2+p)d_{i+2}+3p(p-1)(i+1+2p)d_{i+1}+(p-1)(2p-1)(i+3p)d_i>6p^2(i+2+p)d_{i+2}+3p(p-1)(i+1+2p)d_{i+1}+(p-1)(2p-1)(i+3p)d_{i+1}=6p^2(i+2+p)d_{i+2}+(p-1)[3p(i+1+2p)+(2p-1)(i+3p)]d_{i+1}$. 6p^3(i+3)d_{i+3}=6p^2(i+2+p)d_{i+2}+3p(p-1)(i+1+2p)d_{i+1}+(p-1)(2p-1)(i+3p)d_i>6p^2(i+2+p)d_{i+2}+3p(p-1)(i+1+2p)d_{i+1}+(p-1)(2p-1)(i+3p)d_{i+1}=6p^2(i+2+p)d_{i+2}+(p-1)[3p(i+1+2p)+(2p-1)(i+3p)]d_{i+1}$. This shows$6p^3(i+3)d_{i+3}\ge 6p^2(i+2+p)d_{i+2}+(p-1)[3p(i+1+2p)+(2p-1)(i+3p)]d_{i+1} \$. Done.

1